Energy Use in Greenhouses in the EU: A Review Recommending Energy Efficiency Measures and Renewable Energy Sources Adoption - Bas Paris; Foteini Vandorou; Athanasios T. Balafoutis; Konstantinos Vaiopoulos; George Kyriakarakos; Dimitris Manolakos; George Papadakis (Applied Sciences, 2022)
This study conducts a review of energy use in the EU greenhouse agriculture sector. The studies presented illustrate that energy use in greenhouses is varied and generally dependent on fossil sources. High energy systems, which are more dominant in northern Europe, are generally heavily climate controlled and energy use is dominated by heating and cooling processes, while low energy systems, which are dominant in southern Europe, show a mixture of energy uses including heating, cooling, irrigation, lighting, fertilisers, and pesticides. Our review also provides a discussion of energy efficiency measures and renewable energy sources adoption for greenhouse production. Finally, our review indicates that accurate and reliable studies on energy use in greenhouse production are scarce and fragmented and that a range of differing methodologies are currently used to estimate on-farm energy use. The development of a comprehensive methodology and categorisation for measuring energy use in greenhouse agricultural production would, in our view, catalyse further studies in this sector, considerably improve our understanding of energy use in greenhouses and support the green transition. Based on this, this paper proposes a basic framework for measuring energy use in greenhouse agriculture.